2004
DOI: 10.1007/s10347-004-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental model for Eocene foraminiferal limestones of the Adriatic carbonate platform (Istrian Peninsula)

Abstract: The foraminiferal limestones from the Middle Eocene Central Istrian region illustrate progressive deepening of depositional gradients. Shifting of Lower Cuisian to Upper Lutetian microfacies can be described in terms of a ramp model. The Orthophragminae-bearing parts of the foraminiferal limestones are interpreted in terms of larger foraminiferal faunal associations, planktonic foraminiferal relative abundance, limitations of algal endosymbionts, foraminiferal lamellar thickness and flattening of test shapes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 30 publications
(45 reference statements)
2
75
0
Order By: Relevance
“…3) North Adriatic platform (38°N) The Palaeogene succession of the North Adriatic platform reveals the existence of larger benthic foraminifera-dominated assemblages without corals during the Ypresian and Lutetian (Cosovic et al 2004;Zamagni et al 2008). The first coral records after the Palaeocene-Eocene Thermal Maximum point to the uppermost Lutetian (SBZ 16; Cosovic et al 2004).…”
Section: Circum-tethyan Carbonate Platform Evolution During the Palaementioning
confidence: 99%
See 1 more Smart Citation
“…3) North Adriatic platform (38°N) The Palaeogene succession of the North Adriatic platform reveals the existence of larger benthic foraminifera-dominated assemblages without corals during the Ypresian and Lutetian (Cosovic et al 2004;Zamagni et al 2008). The first coral records after the Palaeocene-Eocene Thermal Maximum point to the uppermost Lutetian (SBZ 16; Cosovic et al 2004).…”
Section: Circum-tethyan Carbonate Platform Evolution During the Palaementioning
confidence: 99%
“…The first coral records after the Palaeocene-Eocene Thermal Maximum point to the uppermost Lutetian (SBZ 16; Cosovic et al 2004). A significant increase in coral abundance is recorded from the Early Oligocene in successions in Slovenia and in the Po Basin (Nebelsick et al 2005).…”
Section: Circum-tethyan Carbonate Platform Evolution During the Palaementioning
confidence: 99%
“…The presence of large and numerous discocyclinids is usually interpreted as an indication of a stable, normal marine environment (Cosovic et al, 2004), and it is generally accepted that larger individuals are commonly found in environments characterized by optimal conditions for a given species (Cosovic and Drobne, 1995). Discocyclinids were described from Eocene carbonates of northern Italy in association with nummulites from the upper part of the outer shelf (Bassi, 2005), while in more distal environments, discocyclinids which could presumably tolerate water depths of up to 100 m were dominant (Geel, 2000).…”
Section: A3 Bioclastic Extraclastic Grainstonementioning
confidence: 99%
“…In the Tethyan region, large accumulations of LBF were generally associated with ramp settings (Buxton and Pedley, 1989) and the relative distribution of different foraminifers across carbonate ramps was used as a valuable tool in paleoenvironmental and paleobathimetric reconstructions (Cosovic et al, 2004;Barattolo et al, 2007). The distribution patterns of fossil LBF were mainly investigated by means of extrapolating environmental proxies gained from extant foraminifers (Beavington-Penney and Racey, 2004) in an attempt to derive parameters such as nutrient and oxygen availability, water chemistry and depth, hydrodynamic energy, and substrate type and stability (Murray, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation